Hybrid approach to calculating proton stopping power in hydrogen - Bailey, Jackson; Kadyrov, Alisher; Abdurakhmanov, Ilkhom; Bray, Igor (2017)
Proton stopping power in hydrogen is calculated using a hybrid method. A two-centre convergent close-coupling method is used for calculations involving the proton fraction of the beam, while the Born approximation is used for the hydrogen fraction. For proton-hydrogen collisions rearrangement processes are explicitly included via a two-centre expansion. Hydrogen-hydrogen collisions are calculated including one- and two-electron processes. Despite using the first-order approximation in the hydrogen-hydrogen channel, overall reasonably good agreement with experiment is seen above 100 keV. © Published under licence by IOP Publishing Ltd.